2010
DOI: 10.1371/journal.pgen.1001065
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Profiling of p63 DNA–Binding Sites Identifies an Element that Regulates Gene Expression during Limb Development in the 7q21 SHFM1 Locus

Abstract: Heterozygous mutations in p63 are associated with split hand/foot malformations (SHFM), orofacial clefting, and ectodermal abnormalities. Elucidation of the p63 gene network that includes target genes and regulatory elements may reveal new genes for other malformation disorders. We performed genome-wide DNA–binding profiling by chromatin immunoprecipitation (ChIP), followed by deep sequencing (ChIP–seq) in primary human keratinocytes, and identified potential target genes and regulatory elements controlled by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
220
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(233 citation statements)
references
References 96 publications
13
220
0
Order By: Relevance
“…SHFMrelated genes are likely to participate in complex networks that involve interactions with one another. Not surprisingly, a search of TP63 binding sites revealed locations within 300 kb of genes at many of the other SHFM loci, suggesting that these sites may constitute regulatory elements contributing to SHFM [Kouwenhoven et al, 2010].…”
Section: Clinical Aspects Genetic Aspects and Nosographymentioning
confidence: 99%
See 1 more Smart Citation
“…SHFMrelated genes are likely to participate in complex networks that involve interactions with one another. Not surprisingly, a search of TP63 binding sites revealed locations within 300 kb of genes at many of the other SHFM loci, suggesting that these sites may constitute regulatory elements contributing to SHFM [Kouwenhoven et al, 2010].…”
Section: Clinical Aspects Genetic Aspects and Nosographymentioning
confidence: 99%
“…A deletion involving DSS1, SLC25A13, and part of DYNC1I1, which are centromeric to DLX5/6, was described in a patient with isolated split-foot malformations [Kouwenhoven et al, 2010]. Multiple TP63 binding sites were identified in the deleted region, including one (designated SHFM1-BS1) that was shown to respond to TP63 transactivation and physically associate with the DLX6 promoter, and whose enhancer activity correlated with the expression patterns of Dlx5/6 in the AER of zebrafish fins and mouse limbs.…”
Section: Balanced/unbalanced Chromosome Rearrangementsmentioning
confidence: 99%
“…We speculate that p53 or p63 enrichment on myogenin regulatory elements previously observed in non-myogenic cells, such as MEFs, 41 mESC, 42 or primary keratinocytes, 46 may reflect a poised global surveillance system that maintains cell identity and prevents, at least, a myogenic fate transition in response to stress signals. This notion is supported by the observation that elimination of p53 enhances cellular plasticity and efficiency of reprogramming somatic cells to pluripotency 58 and differentiated hepatocytes to malignant cell fates.…”
Section: Discussionmentioning
confidence: 78%
“…Instead, we analyzed a published human p63 ChIP-seq data set based on the observation that p63, a p53 family member, is estimated to bind 61.8 to 82.3% of p53 target genes. 41 We found two p63-binding sites at positions − 7962 and − 5679 on the human myogenin promoter based on a genome-wide profiling of p63-binding sites using human primary keratinocytes cultured under the non-stressed growth condition 46 ( Figure 3a Repression of myogenin by p53 is partially mediated through a distal enhancer region upstream of the mouse myogenin gene. Global ChIP sequencing analysis has shown that p53-repressed genes tend to associate with p53 peak enrichment at the distal enhancers in mESC exposed to doxorubicin.…”
Section: Resultsmentioning
confidence: 96%
“…miR-130b is an exonic miRNA located on chromosome 22. To investigate whether the expression of these miRNAs could be directly controlled by p63, we analyzed miR-138-2, miR-181a/b-1, and miR-130b genomic regions to identify p63-responsive elements using a genome-wide p63 DNA-binding profile previously generated in human skin keratinocytes (26,27). In close proximity (within 25 kb) to these miRNA genes, we found highly reliable p63-binding sites (BS) (Fig.…”
Section: Sirt1 or P63 Silencing By Sirna Induces Senescence In Prolifmentioning
confidence: 92%